(untitled) (Current Horticulture, 2024)
Three essential heavy metal containing chemicals, viz. MnSO4, CuSO4 and ZnSO4 were used at three concentrations to study their influence on content of leaf pigments, viz., chlorophylls and carotenoids in tuberose cv. ’Prajwal’. The experiment was conducted at College of Horticulture, Dr Y.S.R. Horticultural University, Anantharajupeta village, Kadapa district of Andhra Pradesh, following the polybag culture, in a Completely Randomized Design with factorial concept using three replications. Data recorded on the content of chlorophylls and carotenoids in the leaves of tuberose cv. ’Prajwal’ were analyzed statistically using OPSTAT software and the least significant difference was used to differentiate the treatments. Statistical analysis of results indicated that application of ZnSO4 @ 400 mg/kg soil recorded a significant improvement in contents of chlorophyll-a (0.047, 0.074 and 0.060) and chlorophyll-b (0.029, 0.059 and 0.044) mg/g fresh weight of leaves respectively during 2018- 19, 2019-20 and the pooled data analysis, whereas total chlorophylls content (0.058 mg/g fresh weight of leaves)was found significant only during 2018-19.Significantly highest total carotenoids content (1.77, 2.43 and 2.10 mg/g fresh weight of leaves) was recorded respectively during 2018-19, 2019-20.